2011
DOI: 10.1186/1471-2458-11-812
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of the human resource policy implications of voluntary counselling and testing scale-up in Kenya: applying a model for policy analysis

Abstract: BackgroundKenya experienced rapid scale up of HIV testing and counselling services in government health services from 2001. We set out to examine the human resource policy implications of scaling up HIV testing and counselling in Kenya and to analyse the resultant policy against a recognised theoretical framework of health policy reform (policy analysis triangle).MethodsQualitative methods were used to gain in-depth insights from policy makers who shaped scale up. This included 22 in-depth interviews with Volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Similar findings in research on anaemia management in ANC in East Java [2] suggest this may be relevant to other areas across Indonesia. Evidence from other contexts supports the hints in our data that potential obstacles within regulation, personnel roles and training are in politics with laboratory staff in relation to task-shifting, and in ensuring equity even in outreach areas [54][55][56]. Operational research alongside political prioritisation has been shown to inform and facilitate interventions in staff training and supervision, both identified as needs in our study, leading to improved antenatal testing rates [57].…”
Section: Discussionsupporting
confidence: 79%
“…Similar findings in research on anaemia management in ANC in East Java [2] suggest this may be relevant to other areas across Indonesia. Evidence from other contexts supports the hints in our data that potential obstacles within regulation, personnel roles and training are in politics with laboratory staff in relation to task-shifting, and in ensuring equity even in outreach areas [54][55][56]. Operational research alongside political prioritisation has been shown to inform and facilitate interventions in staff training and supervision, both identified as needs in our study, leading to improved antenatal testing rates [57].…”
Section: Discussionsupporting
confidence: 79%
“…A summary of draft findings was additionally circulated within the ZPS to garner feedback. Our approach was guided by recognized qualitative analysis techniques including reading for content, coding, data reduction, data display and interpretation ( Yin 2009 ; Cataldo et al 2011 ; Taegtmeyer et al 2011 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Where the offer of testing is not routine (such as in general outpatients or in-patient wards), uptake can be patchy with success dependant on local programmes, policies and staffing. PITC in these settings has been delivered largely through a task-shifting approach using either dedicated lay counsellors (Taegtmeyer et al, 2011 ), who require additional funding and are trained in a longer counselling protocol intended for the voluntary counselling and testing (VCT) approach; or nurses, many of whom have dual roles (Evans & Ndirangu, 2011 ).…”
Section: Introductionmentioning
confidence: 99%